IS FOREIGNNESS A SOURCE OF COMPETITIVE ADVANTAGE IN THE BRAZILIAN PHARMACEUTICAL INDUSTRY? - Monteiro, Ricardo Itapema de Castro; Sheng, Hsia Hua (Revista Mineira de Contabilidade, 2021)
During the first decade of the 21st century, the accelerated growth of the pharmaceutical market in Brazil attracted investments from multinational pharmaceutical companies. National companies followed this investment trend, and the industry matured, and competition intensified. However, companies that operate in a foreign, new environment, driven by unfamiliar competitive forces encounter additional costs to operate. Using data from 2011 to 2016, this study employs panel data methodology with fixed effects using a sample of twenty-two pharmaceutical companies, eleven Brazilian subsidiaries of multinationals and eleven national companies, with the objective to investigate whether foreign companies operating in Brazil incur a liability of foreignness (LOF), which refers to these additional operating costs. This study contributes to the literature by evaluating the impact of Liability of Foreignness on working capital and profitability in the pharmaceutical sector. Our findings suggest that MNEs have a competitive disadvantage in inventory management compared to local companies.